2013
DOI: 10.1016/s0034-7094(13)70206-x
|View full text |Cite
|
Sign up to set email alerts
|

Pain Management in Burn Patients

Abstract: Pain management in burn patients is still a challenge for the multidisciplinary team. Frequent and continuous evaluation of the patient's response is very important due to the various stages that the hospitalized burn patient goes through, as well as a combination therapy with analgesic and non-pharmacological measures. Understanding the complexity of the pathophysiological, psychological, and biochemical changes a burn patient presents is the first step to achieve success in analgesic management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(9 citation statements)
references
References 46 publications
0
9
0
Order By: Relevance
“…The various dimensions of pain intensity are associated with different areas of the pain network. Changes in the pain and motor network have been observed when chronic pain occurs in burn patients [ 29 ]. The treatment mechanism of ST is known to inhibit pain by stimulating C fibers of afferent pathways with five artificial electrical stimulation and blocking the pathways of pain information [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The various dimensions of pain intensity are associated with different areas of the pain network. Changes in the pain and motor network have been observed when chronic pain occurs in burn patients [ 29 ]. The treatment mechanism of ST is known to inhibit pain by stimulating C fibers of afferent pathways with five artificial electrical stimulation and blocking the pathways of pain information [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Many studies of non-invasive brain-modulatory therapy have demonstrated a relationship between changes in the cerebral pain network and pain intensity. This pain network consists of the primary and secondary somatosensory cortex, the prefrontal lobe, dorsolateral prefrontal cortex, and medial prefrontal cortex [ 29 ]. Neuroimaging studies indicate that the dorsolateral prefrontal cortex may play a role in a top-down mode of inhibition via fibers descending from the prefrontal cortex, which may modulate pain perception.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Along with initial pain, there may be incidental pain with significant severity variation, leading to changes in analgesic requirements. 4 In the acute phase, it is estimated that 84% of patients experience severe to intolerable pain, 100% report daily pain, and 92% suffer night pain that awakens them. 5 …”
Section: Introductionmentioning
confidence: 99%
“…Acute stress disorder, post-traumatic stress disorder, chronic pain and depression are highly prevalent among survivors of severe burns (1). Anesthetic management may modulate this physiological response and impact post-operative recovery.…”
Section: Introductionmentioning
confidence: 99%